Answer:
![y=(-4)/(3)x+1](https://img.qammunity.org/2023/formulas/mathematics/college/lnk9ufeplukoiip79htcggsnidxiaktbdf.png)
Explanation:
perpendicular means negative reciprocal of the gradient
y = ¾x - 1 is perpendicular to y =
![(-4)/(3)x-1](https://img.qammunity.org/2023/formulas/mathematics/college/gczb6dvdo8f477k31z0f3bgc0i631uueu7.png)
now we need to workout what the y intercept should be to make the sides equal. let's take away -1 for now
![y=(-4)/(3)x](https://img.qammunity.org/2023/formulas/mathematics/college/69ojwtjams7ac5dy0pvidv1jibak4a8jhv.png)
![-3=(-4)/(3)(3)](https://img.qammunity.org/2023/formulas/mathematics/college/pj57x4yu9yxbnajnjb383jc9ly5e87482a.png)
-3 = -4
To get from -4 to -3, you have to add 1. Therefore the y intercept is one. This means the final equation is:
![y=(-4)/(3)x+1](https://img.qammunity.org/2023/formulas/mathematics/college/lnk9ufeplukoiip79htcggsnidxiaktbdf.png)